Evaluating the impact of Africa Growth and Opportunity Act (AGOA) in South Africa's economy - Ndlovu, Simphiwe (Research of GSB, 2018)
Several studies have examined the relationship between trade liberalisation policies, economic growth and development. These existing studies have in many ways overlooked the role played by Africa Growth and Opportunity Act (AGOA) since its inception as early as 2000. This study attempts to highlight and evaluate the role of AGOA within a South African economy context through the use of inductive quantitative research technique. The auto-regressive distributed lag (ARDL) framework was used in the bound testing cointegration process, which enabled the researcher to obtain the current impact on trade liberalisation and economic growth under AGOA in South Africa. Since the study used ARDL to test AGOA benefits in human capital, capital investment, unemployment rate and trade liberation means of finding interchanging of ideas between South Africa and United State of America and importantly the improved economic growth. The results showed no improvement in human capital, stagnant unemployment rate, no evidence of South Africa economy transformed into knowledge based economy; the transfer of investment in South Africa through AGOA legislation does not show an improving economy and this could be coursed by the tertiary sector growing faster relative to other sectors. The study concludes that the AGOA deals must at least ensure the USA firms are opening new branches in South Africa which will create new jobs and with the outcome of the production of goods and services which will directly increase the demand of highly skilled work force.